Elucidating the Role of Microstructure in Thiophosphate Electrolytes – a Combined Experimental and Theoretical Study of β‐Li3PS4. Issue 18 (24th April 2022) - Ates, Tugce; Neumann, Anton; Danner, Timo; Latz, Arnulf; Zarrabeitia, Maider; Stepien, Dominik; Varzi, Alberto; Passerini, Stefano
Abstract: Solid‐state batteries (SSBs) are promising candidates to significantly exceed the energy densities of today's state‐of‐the‐art technology, lithium‐ion batteries (LIBs). To enable this advancement, optimizing the solid electrolyte (SE) is the key. β ‐Li3 PS4 ( β ‐LPS) is the most studied member of the Li2 S‐P2 S5 family, offering promising properties for implementation in electric vehicles. In this work, the microstructure of this SE and how it influences the electrochemical performance are systematically investigated. To figure this out, four batches of β ‐LPS electrolyte with different particle size, shape, and porosity are investigated in detail. It is found that differences in pellet porosities mostly originate from single‐particle intrinsic features and less from interparticle voids. Surprisingly, the β ‐LPS electrolyte pellets with the highest porosity and larger particle size not only show the highest ionic conductivity (up to 0.049 mS cm –1 at RT), but also the most stable cycling performance in symmetrical Li cells. This behavior is traced back to the grain boundary resistance. Larger SE particles seem to be more attractive, as their grain boundary contribution is lower than that of denser pellets prepared using smaller β ‐LPS particles. Abstract : Overview on the relationship of particle size and pellet porosity versus ionic conductivity of β ‐LPS thiophospate.